Synergistic Antitumor Effect of a Combination of Paclitaxel and Carboplatin with Nobiletin from Citrus depressa on Non-Small-Cell Lung Cancer Cell Lines - Uesato, Shinichi; Yamashita, Hirofumi; Maeda, Ryu; Hirata, Yoshiyuki; Yamamoto, Maho; Matsue, Saki; Nagaoka, Yasuo; Shibano, Makio; Taniguchi, Masahiko; Baba, Kimiye; Ju-ichi, Motoharu (Planta Medica, 2014)
Non-small-cell lung carcinomas do not sufficiently respond to cancer chemotherapeutic drugs. Combination effects of cancer chemotherapy drugs (paclitaxel and carboplatin) with nobiletin or powdered Shiikuwasha extract from Citrus depressa were examined by isobologram and combination index analyses. It was demonstrated that the combination generated a synergistic inhibitory effect against the proliferation of the human non-small-cell lung carcinoma cell lines A549 and H460 and that of the two chemotherapy drugs, paclitaxel was responsible for this synergistic effect. Furthermore, the percentage of apoptotic cells was decreased with increasing rates of nobiletin to paclitaxel and carboplatin. These findings were considered to be attributed to the ability of nobiletin to regulate cells in the G1 phase, which escaped cell death initiated by paclitaxel and carboplatin. An antitumor activity assay showed that this combination significantly suppressed the growth of subcutaneous A549 tumor xenografts in nude mice.
Keywords: nobiletin; Citrus depressa; Rutaceae; non-small-cell lung cancer; cancer chemotherapy drug; synergistic effect; A549 cell xenograft